Evaluating the feasibility of applying cobalt-hydroxyapatite ingots as radiotherapy markers. (September 2020) - Lin, Wei-Chun; Tang, Cheng-Ming; Lu, Cheng-Chang; Chuang, Chun-Chao
Graphical abstract: Abstract: The substitution of cobalt for calcium in hydroxyapatite produces CoHA with a higher effective atomic number. This study evaluates various medical imaging characteristics of round CoHA ingots in a porcine phantom to demonstrate the feasibility of using CoHA ingots as radiotherapy markers. CoHA was compressed into round ingots and then implanted into a porcine liver phantom and a gelatin porcine vertebra phantom along with three commercially available radiotherapy markers. The phantom was respectively scanned and photographed using a routine x-ray imager, magnetic resonance imager, computed tomography (CT) imager, and ultrasound imager followed by image analysis in ImageJ software. CoHA ingots could be clearly identified with general imaging instruments (x-ray, CT, and ultrasound) and the image size did not change. There were some metal artifacts in the magnetic resonance images. Biodegradable CoHA ingots can be self-absorbed by the body over time to avoid interference with follow-up disease screening and can be used with most medical imaging instruments quickly to help identify the location and extent of soft-tissue tumors.